2021
DOI: 10.1038/s41598-021-96132-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional grey matter microstructural changes and volume loss according to disease duration in multiple sclerosis patients

Abstract: The spatio-temporal characteristics of grey matter (GM) impairment in multiple sclerosis (MS) are poorly understood. We used a new surface-based diffusion MRI processing tool to investigate regional modifications of microstructure, and we quantified volume loss in GM in a cohort of patients with MS classified into three groups according to disease duration. Additionally, we investigated the relationship between GM changes with disease severity. We studied 54 healthy controls and 247 MS patients classified rega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Infarct segmentation and registration to the standard MNI-152 brain template were performed in accordance with the previous published articles (Biesbroek et al, 2019 ). First, acute infarct lesions were segmented manually on DWI sequence using the ITK-SNAP software (Solana et al, 2021 ). Accordingly, a lesion mask was generated for each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Infarct segmentation and registration to the standard MNI-152 brain template were performed in accordance with the previous published articles (Biesbroek et al, 2019 ). First, acute infarct lesions were segmented manually on DWI sequence using the ITK-SNAP software (Solana et al, 2021 ). Accordingly, a lesion mask was generated for each subject.…”
Section: Methodsmentioning
confidence: 99%
“…However, FA changes in the thalamus in MS are controversial. Some studies have reported decreased FA in the thalamus of MS patients [27] , [28] while others showed increased FA values [3] , [23] , [29] , [30] .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, most GM regions showed connectivity changes, particularly in strength and closeness centrality. The atrophy of deep GM areas occurs in early stages of MS, and extends to multimodal cortical regions over time ( Eshaghi et al, 2018 ; Solana et al, 2021 ). In this context, we demonstrated that the network metrics applied to the new multilayer framework can pick up relevant network alterations in MS in most deep GM and in some cortical regions involved in visual areas (bilateral occipital and lingual areas) and cognition ( Gabilondo et al, 2014 ; Riccitelli et al, 2020 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%